2019
DOI: 10.1007/s00198-018-04817-3
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, bone density relative to body weight and prevalent vertebral fracture at age 62 years: the Newcastle thousand families study

Abstract: Obesity is a global epidemic and there remains uncertainty over the effect of obesity on skeletal health, particularly in the context of osteoporosis. The aim of this study was to 7 investigate associations of body mass index (BMI) and obesity with bone mineral density (BMD) and prevalent vertebral fracture (VF) in men and women aged 62 years. Three hundred and forty two men and women aged 62.5 ± 0.5 years from the Newcastle Thousand Families Study birth cohort, underwent DXA evaluations of femoral neck and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Moreover, the bone health is often deteriorated in individuals with increased fat mass (Shapses et al, 2017). The prevalence of vertebral fractures are higher in individuals with obesity (Rudman et al, 2019) and the occurrence of osteoporosis, particularly in postmenopausal women, is associated with increased body weight (Hsu et al, 2006). High-fat diet-induced body weight gain enhance bone resorption and elevate osteoclasts in bone marrow (Cao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bone health is often deteriorated in individuals with increased fat mass (Shapses et al, 2017). The prevalence of vertebral fractures are higher in individuals with obesity (Rudman et al, 2019) and the occurrence of osteoporosis, particularly in postmenopausal women, is associated with increased body weight (Hsu et al, 2006). High-fat diet-induced body weight gain enhance bone resorption and elevate osteoclasts in bone marrow (Cao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies on osteoporosis have been conducted in males than in females. Recent studies indicated that visceral adipose tissue was also a risk factor for osteoporosis in men [4,17] and that obese men were more likely to have vertebral fracture than men of normal weight [5]. Another study indicated that obesity induced by a HFD aggravated bone loss in the cancellous bone compartment, with a greater loss in males than females [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared to women of normal weight, obese women were more likely to have at least one vertebral fracture and at least one mild vertebral deformity. Obese men were more likely to have a moderate and/or severe vertebral fracture compared to men of normal weight [5]. However, no specific pharmacotherapy has been approved.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the T scores do not take into account BMI. Obesity protects from osteoporosis but the relative BMD for BMI may be lower in obese women compared with normal‐weight women, which might contribute to a higher risk of fractures …”
Section: Discussionmentioning
confidence: 99%
“…Obesity protects from osteoporosis but the relative BMD for BMI may be lower in obese women compared with normal-weight women, which might contribute to a higher risk of fractures. 31 One previous cohort study of 480 women, among whom 96 had GDM, reported greater BMD losses from early pregnancy to third trimester of pregnancy in women with GDM compared with women without GDM. 32 Within women with GDM, lower initial BMD values, higher fat accumulation and higher early-pregnancy BMI were associated with lower BMD loss.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 98%